2009
DOI: 10.1152/ajpgi.90640.2008
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PPARγ by rosiglitazone attenuates intestinal Clsecretion

Abstract: The thiazolidinedione (TZD) drugs rosiglitazone (Ro) and pioglitazone (Po) are PPARgamma agonists in widespread clinical use as insulin-sensitizing agents in Type 2 diabetes. On the basis of recent evidence implicating PPARgamma as a positive modulator of intestinal epithelial differentiation, we hypothesized that TZD drugs might attenuate intestinal secretory function. To evaluate this possibility, we examined the effects of Ro and Po on electrogenic Cl- secretion [short-circuit current (I(sc))] in mouse inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 53 publications
3
18
0
Order By: Relevance
“…Methods were similar to those described previously [18,[32][33]. As with these previously reported studies, we demonstrated a single band with the expected molecular weight of ~170 kD for CFTR.…”
Section: Total Cftr Protein Expressionsupporting
confidence: 85%
See 1 more Smart Citation
“…Methods were similar to those described previously [18,[32][33]. As with these previously reported studies, we demonstrated a single band with the expected molecular weight of ~170 kD for CFTR.…”
Section: Total Cftr Protein Expressionsupporting
confidence: 85%
“…Jejuna were later prepared for western blot analysis by homogenization. The western blot protocol was similar to that described previously [18]. Briefly, samples were analyzed for protein content, and ran on 4-12% Bis-Tris gels at 150 volts for ~ 1.5 hours.…”
Section: Cftr Western Blotmentioning
confidence: 99%
“…Since, CFTR chloride channels provide the major route for chloride secretion into the jejunum lumen, we determined total CFTR protein present utilizing standard western blot techniques [18,[28][29][30]. We confirmed a single band with the expected molecular weight of ~170 kD for CFTR.…”
Section: Total Cftr Nkcc1 and Na + /K + -Atpase Protein Expression Smentioning
confidence: 69%
“…Oral administration of rosiglitazone to mice for 8 d reduces intestinal forskolinstimulated anion secretion and substantially inhibits choleratoxin-induced intestinal fluid accumulation. 15 In HT29 intestinal cells, 5 d of treatment with rosiglitazone inhibits cAMP-dependent Cl Ϫ secretion concomitantly with a decrease in the protein expression of CFTR, Na…”
mentioning
confidence: 99%
“…15 Thus, the strongest and most consistent evidence to date suggests that the primary effect of PPAR␥ agonists in polarized epithelia is a decrease in the expression of Cl Ϫ channels. In summary, a compendium of data suggests that PPAR␥ agonists cause fluid retention through effects on the renal collecting duct.…”
mentioning
confidence: 99%